PECULIARITIES OF THE COURSE OF VARIOUS FORMS OF URINARY TRACT INFECTIONS IN CHILDREN AT THE PRESENT STAGE - Vodianyk , A. A.; Grechukha , Y.O.; Gniloskurenko , A.V.; Mitiuriaeva-Kornijko , I.O. (The Ukrainian Scientific Medical Youth Journal, 2017)
Urinary tract infections (UTIs) are one of the most common bacterial infections and causes of hospitalization in children. A well-established diagnosis and proper treatment are provided by primary care physicians and, quite often, it is a difficult task because the symptoms are nonspecific. The purpose of this work was to determine the characteristics of the flow of urinary infections in children at the present stage. The study was attended by 86 patients undergoing treatment at children’s clinics N° 6 and №7 in Kyiv during the course of various forms of urinary tract infections. The study analyzed the data obtained from anamnesis, objective examination and the results of laboratory and instrumental studies. The leading syndrome in patients with UTI was intoxication (27% - infections of the lower urinary tract, 44% - acute pyelonephritis (AP), 52% - recurrence of chronic pyelonephritis (CP)). In most cases, AP and CP showed shift of leukocyte formula to the left in 93% and 94% of cases respectively. The most frequent ultrasound indicators of pyelonephritis were renal pelvic dilatation: 36% in patients with AP, and 63% in patients with CP, consolidation of median complex: 81% - AP, 85% - CP. Among the diseases that accompanied urinary tract infections, the most common in the INSS group was urinary incontinence (15%), anatomical anomalies were detected in 8% of patients with chronic pyelonephritis. At the present stage, cases of acute pyelonephritis and relapses of chronic pyelonephritis are often revealed in the absence of specific complaints in patients, as well as unexpressed inflammatory changes in the overall blood test and general urinalysis.